Foreign Investment in Emerging Markets: International Diversification or Familiarity Bias?. Issue 10 (9th August 2018) - Liu, Yunxiao; Park, James L.; Sohn, Bumjean
ABSTRACT: This study empirically tests whether foreign investors take advantage of international diversification when investing in emerging Asian markets. Using the 2007–2008 financial crisis as identification, we find that firms with higher foreign ownership had better stock returns during the financial crisis. Moreover, the diversification effect exists in five out of the eight emerging markets and is stronger in markets with a lower dynamic conditional correlation with the global market index. We also find that foreign investors prefer firms with a lower international sales ratio. In conclusion, the evidence consistently suggests that foreign investors take advantage of diversification effects.